Assessing the Role of Educational Interventions in Shaping Students’ Earthquake Preparedness Attitudes - Dr. Sidra Kiran; Shafqat Ibrahim; Humna; Wajid Mahnaz (Research Journal of Psychology, 2025)
The frequency and intensity of earthquakes have increased in many regions, underscoring the importance of institutionalized disaster education. The study aimed at “Assessing the Role of Educational Interventions in Shaping Students’ Earthquake Preparedness Attitudes”. The objectives of the study were, 1) To measure the attitude of school employees towards the need of disaster management training during earthquake at school level. 2) To measure the attitude of students towards the need of disaster management training during earthquake at school level. . The population for this research comprised employees working in higher secondary schools in the Rawalpindi/Islamabad area who are involved in disaster management, including both trained and untrained personnel, for the academic year 2023–2025. In the study, the sample size was expanded to increase the robustness and generalizability of the findings. The total population remained the same, comprising 1,480 students and 300 teachers. The sample included 148 students and 30 teachers, with a total sample size of 178 participants. Similar to the pilot study, the final study also achieved a 100% response rate. The findings suggest that while 90% of respondents feel confident that disaster management training prepares them for earthquakes, concerns remain regarding emergency supplies, with 90% believing classrooms lack essential resources. Additionally, 73% trust that structural safety checks are conducted, but 60% feel evacuation plans are not well-practiced, highlighting gaps in preparedness. Hence, it is recommended that schools should conduct a thorough assessment of emergency supply stockpiles and ensure that all classrooms and common areas are well-equipped. Regular evacuation drills should be conducted in collaboration with emergency response teams to improve students' familiarity with evacuation procedures. Moreover, periodic structural safety inspections should be reinforced with transparent reporting to build trust in school infrastructure integrity.